The prevalence of estrogen receptor-1 mutation in advanced breast cancer: The estrogen receptor one study (EROS1). (2019) - Najim, Omar; Huizing, Manon; Papadimitriou, Konstantinos; Trinh, Xuan Bich; Pauwels, Patrick; Goethals, Sofie; Zwaenepoel, Karen; Peterson, Kevin; Weyler, Joost; Altintas, Sevilay; van Dam, Peter; Tjalma, Wiebren
Abstract: Background: Breast cancer has, due its high incidence, the highest mortality of cancer in women. The most common molecular variety of breast cancer is luminal subtype that expresses estrogen and progesterone receptors. Estrogen receptor alpha (ERα), encoded by the estrogen receptor1 (ESR1) gene, is expressed in approximately 70% of all breast cancers, and hormonal therapy represents a major treatment modality in all stages of ER positive breast cancers. Acquired mutations in the ligand-binding domain (LBD) of ERα, referred as ESR1 mutation, result in resistance to different endocrine therapies leading to disease progression or recurrence. Recent studies reviled that these ESR1 mutations lead to constitutive activity of the estrogen receptor ER, meaning that the receptor is active in absence of its ligand conferring resistance against endocrine therapy and tumor growth. Published studies have not yet been able to determine the exact prevalence rate of ESR1 mutations, but set the outer boundaries between 11–55%. Purpose: The goal of the present study is to determine the frequency rate of ESR1 mutations in ER positive recurrent breast cancer by using digital droplet PCR (ddPCR) technique. Materials and methods: This retrospective study was conducted in the Multidisciplinary Breast Clinic of Antwerp University Hospital. The seven most common ESR1mutations (c.1138G>C (p. (E380Q)), c.1610A>G (p.(Y537C)), c.1613A>G (p.(p.D538G)), c.1607T>G (p.(L536R)), c.1387T>C (p.S463R)), c.16410A>C (p.(Y537S)), c.609T>A (p.(Y537N)) were assessed in available baseline plasma samples of 21 patients with ER positive recurrent breast cancer. Inclusion criteria for study participation were: female, age above 18 years, ER positive breast cancer, 5years adjuvant hormonal therapy of primary disease, and disease recurrence or metastasis during or after stop of endocrine therapy. ESR1 mutations were analyzed in cell-free DNA (cfDNA) by using digital droplet PCR (ddPCR). Results: cfDNA was obtained from 21 patients with recurrent breast cancer. ESR1 mutations were found in 4/21 (19%; 95% CI, 5%–42%). The test sensitivity was lower than the targeted value <0.1% in 29% of patients (6/21). No significant statistical difference in baseline clinical characteristics was observed in patients with wild-type and mutant ER ( p >0.05). Adjuvant endocrine therapy for primary disease was Tamoxifen (TAM) for 57% of patients (12 of 21) of whom 8 patients had received aromatase inhibitor (AI) after two years, while 43% of patients (9 of 21) had received AI as first line adjuvant hormonal therapy. All the patients had received aromatase inhibitor AI therapy in first or second line therapy with initially a variable period of good response. Conclusion: ESR1 mutation analysis could be determined in archived plasma samples using simple non-invasive methods. In the future, screening for mutation status could improve the therapeutic strategies in controlling ER signaling before the occurrence of wide spread disease metastasis.